ifo World Economic Survey August 2019 - Dorine Boumans; Johanna Garnitz (ifo World Economic Survey, 2019)
World Economic Climate: ifo World Economic Climate Deteriorates Advanced Economies: Previous Uptick in Confidence in Advanced Economies Vanishes Emerging and Developing Economies: Emerging Markets and Developing Economies Face a Renewed Downturn: Special Box The South Caucasus Countries between Russia and the European Union Special Topic: Measuring Experts' Macroeconomic Models
Keywords: 330